2019
DOI: 10.1182/blood.2019001285
|View full text |Cite
|
Sign up to set email alerts
|

Oral 5-azacytidine and romidepsin exhibit marked activity in patients with PTCL: a multicenter phase 1 study

Abstract: The authors report a phase 1 study of romidepsin combined with oral 5-azacytidine in patients with relapsed/refractory lymphomas, including complete remissions in 3 patients with angioimmunoblastic T-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 23 publications
2
76
1
Order By: Relevance
“…Experimentally, HDAC inhibitor chidamide significantly inhibited the growth of EP300-mutated T-lymphoma cells and KMT2D-mutated T-lymphoma cells when combined with the hypomethylating agent decitabine [12]. Clinically, a phase 1 study of HDAC inhibitor romidepsin and hypomethylating agent 5azacytidine exhibited marked activity in patients with PTCL, with ORR and CR of 73% and 55%, respectively [32]. Therapeutic efficacy of novel small molecules like IDH2 inhibitors targeting IDH2, or modulators of the SWI/SNF chromatin complex targeting ARID1B could also be explored in PTCL.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, HDAC inhibitor chidamide significantly inhibited the growth of EP300-mutated T-lymphoma cells and KMT2D-mutated T-lymphoma cells when combined with the hypomethylating agent decitabine [12]. Clinically, a phase 1 study of HDAC inhibitor romidepsin and hypomethylating agent 5azacytidine exhibited marked activity in patients with PTCL, with ORR and CR of 73% and 55%, respectively [32]. Therapeutic efficacy of novel small molecules like IDH2 inhibitors targeting IDH2, or modulators of the SWI/SNF chromatin complex targeting ARID1B could also be explored in PTCL.…”
Section: Discussionmentioning
confidence: 99%
“…Benigno C. Valdez et al reported that the combination of a hypomethylating agent, decitabine (DAC), a PARP inhibitor and an HDAC synergistically inhibited cell proliferation and induced apoptosis in human leukaemia and lymphoma cells [ 138 ]. A phase I study investigated oral 5-azacytidine (AZA) and romidepsin (ROMI) in patients with PTCL and showed that combination epigenetic modifying drug therapy exhibited marked activity in patients with PTCL [ 139 ]. The PTCL responses to the combination proved durable.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Therefore, novel epigenetic combination treatments based on biological pathophysiology, preclinical data, and clinical efficacy are needed to challenge front-line conventional chemotherapy in the future. 5-Azacytidine and romidepsin combination regimens still suit those patients scheduled for SCT, as reported in a phase I study [ 139 ]. The combination of epigenetic drugs and immune checkpoint inhibitors such as anti-PD1 mAb and lenalidomide are expected to have a good therapeutic effect.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…In addition to these agents, there are drugs in development with some evidence of activity in MTCL, including PI3K inhibitors (duvalisib); proteasome inhibitors (bortezomib and carfilzomib); a host of biologics targeting CD37, CD70, and CD47; and bispecific NK engagers. Figure 4 116,[119][120][121][122][123] shares some data regarding these combinations, recognizing that much of this information has not yet been published in peer-reviewed journals and is available only in abstract form.…”
Section: Development Of Novel:novel Backbonesmentioning
confidence: 99%
“…In a phase 2 study, patients were treated with pembrolizumab at pralatrexate; Romi, romidepsin. 116,[119][120][121][122][123] 200 mg every 21 days. Of 18 patients enrolled, 13 were evaluable for the primary endpoint.…”
Section: Possible New Drugs In Developmentmentioning
confidence: 99%